Impact of Deep Brain Stimulation on Daily Routine Driving Practice in Patients with Parkinson’s Disease - Carsten Buhmann; Eik Vettorazzi; Christian Oehlwein; Fred Rikkers; Monika Poetter-Nerger; Alessandro Gulberti; Christian Gerloff; Christian K. Moll; Wolfgang Hamel (Parkinson's Disease)
Objective. To determine the influence of deep brain stimulation (DBS) on daily routine driving behavior in Parkinson’s disease (PD) patients. Methods. A cross-sectional questionnaire survey was done in 121 DBS-PD patients. The influences of patient characteristics and DBS on current driving and driving at time of surgery and the predictive value of the preoperative levodopa-test on postoperative driving were evaluated. Results. 50% of 110 driving-license holders currently drove. 63.0% rated themselves as safe drivers, 39.4% reported improvement, and 10.9% noted deterioration in driving after DBS surgery. Inactive drivers had quit driving mainly due to disease burden (90.9%). Active drivers were younger, more often males, and less impaired according to H&Y and MMSE, had surgery more recently, and reported more often overall benefit from DBS. H&Y “on” and UPDRS III “off” scores at time of surgery were lower in pre- and postoperative active than in inactive drivers. Tremor and akinesia were less frequent reasons to quit driving after than before DBS surgery. Postoperatively, 22.7% (10/44) of patients restarted and 10.6% (7/66) of patients discontinued driving, independently of H&Y stage. The preoperative levodopa-test was not predictive for the postoperative driving outcome. Conclusion. 50% of PD patients with DBS drive. DBS surgery changes daily routine driving behavior.